?BIOCHEMICAL AND ANTIBACTERIAL STUDIES OF AJOWAN (CARUM COPTICUM) OIL - Qasim, M; Khanb, M Rafiq (Biological Sciences - PJSIR, 2001)
Carum copticum is used for the treatment of gastric and kidney trouble, eye sore, fever, diarrhea, etc (Umar Skii and Krutic 1945). The antibacterial activity of Carum copticum essential oil and fruit was investigated by Kasymova et al (1957). Wahid and Ikram (1961) determined that thymol was the active constituent present in Carum copticum. Singh et al (1980) tested its essential oil for fungicidal activity and reported that these oils were also toxic to some human pathogens. Amira and Khan (1990) studied the antibacterial activity of Carum copticum oil extracted with ethanol and acetone. Ijaz et al (1993) studied the triglycerides of its seeds oil extracted with chloroform at room temperature.